Low-dose computed tomography in elderly pneumonia patients: a need to individualise. Issue 1 (27th July 2018) - Aggarwal, Deepak; Saini, Varinder; Gour, Hitesh
We read with interest the study by Prendki et al. [1], in which the authors proved the diagnostic role of low-dose computed tomography (LDCT) of the thorax in the evaluation of elderly patients with pneumonia. The results showed that addition of LDCT modified the probability of pneumonia in 45% of the patients. However, on comparing with the reference diagnosis, a high discordance rate of 32.2% was found in the LDCT-based diagnosis that needs to be justified [1]. Being an interventional study, the authors should mention the treatment outcomes of all the enrolled patients, particularly those with low probability after LDCT (treated with or without antibiotics). Comparing these outcomes among low/intermediate/high diagnostic groups before and after LDCT might help to reveal a clear picture. Moreover, in view of clinician-labelled diagnosis being the primary outcome in the study, using multiple physicians for better diagnostic agreement might have increased the authenticity of the results. Low-dose computed tomography is an important diagnostic tool in elderly patients with pneumonia; however, its use should be individualised based on patient- and disease-related factors http://ow.ly/sqZs30kuLEX